Genesis 1-11 tales of the earliest world - Good, Edwin M. (Edwin Marshall), 1928- (Palo Alto : Stanford University Press, 2011)
This book invites readers to reconsider what they think they know about the opening chapters of the Book of Genesis, from the creation of the world, through the Garden of Eden, Cain and Abel, the Flood, and the Tower of Babel, to the introduction of Abraham. Edwin M. Good offers a new translation of and literary commentary on these chapters, approaching the material as an ancient Hebrew book. Rather than analyzing the chapters in light of any specific religious position, he is interested in what the stories say and how they work as stories, indications in them of their origins as orally performed and transmitted, and how they do and do not connect with one another. Everyone, from those intimately familiar with Genesis to those who have never read it before, will find something new in Genesis 1-11: Tales of the Earliest World.
Preface; Acknowledgments; Introduction; 1. Genisis in Seven Days; 2. The Garden, Part 1; 3. The Garden, Part 2; 4. Offerings and Their Results; 5. Some Descendants; 6. Some More Descendants; 7. Unusual Births; 8. The Flood(s); 9. Yet Another Curse-and a Blessing; 10. Descendants and Nations; 11. A Tower and a Confusion of Words; 12. A Traditional Genealogy; Coda; Notes
Description based upon print version of record.
Keywords: Bible. -- Commentaries; Bible O.T. Genesis -- Commentaries; Bible O.T.; Bible. O.T. Genesis I-XI -- Commentaries; Religion; RELIGION / Biblical Studies / Old Testament; Electronic books